2012
DOI: 10.1111/j.1600-0897.2012.01145.x
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Peripheral Blood CD4+ CD25high FoxP3+ and CD4+ CD25− FoxP3+ Regulatory T Cells in Normal Pregnancy and Pre‐Eclampsia

Abstract: Our results indicate that the frequency of conventional and non-conventional Tregs alters simultaneously, and the presence in circulation of both of these Treg subsets is similarly important in the adequate development of pregnancy-specific immune tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 25 publications
7
48
2
Order By: Relevance
“…Treg cells in blood of preeclamptic as opposed to healthy pregnant women (19,24,(43)(44)(45)(46)(47)(48)(49), although some previous studies did not show a difference between these groups (32,33,44). In a more recent study, by using an updated phenotyping strategy, Steinborn et al did not find any differences with regard to the whole Treg cell population, while alterations in the preeclampsia group were found in Treg subpopulations (31), in line with our findings (see below).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Treg cells in blood of preeclamptic as opposed to healthy pregnant women (19,24,(43)(44)(45)(46)(47)(48)(49), although some previous studies did not show a difference between these groups (32,33,44). In a more recent study, by using an updated phenotyping strategy, Steinborn et al did not find any differences with regard to the whole Treg cell population, while alterations in the preeclampsia group were found in Treg subpopulations (31), in line with our findings (see below).…”
Section: Discussionsupporting
confidence: 90%
“…In humans, Treg cells are identified as CD4 + T helper cells expressing forkhead box P3 (FOXP3) (14) and high levels of the IL-2 receptor -chain, CD25 (14,15). Early reports indicated that the circulating Treg pool was expanded in normal human pregnancy (17)(18)(19)(20). However, with increasing insights in the complexity of Treg markers in humans, subsequent studies did not report increased frequency in the circulation (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the pathological features that we observed in our in vivo model are compatible with those previously reported in preeclamptic pregnancies, including loss of neutrophil quiescence (22) and reduction of circulating Tregs (40). Preeclampsia is a multiorgan syndrome of pregnancy that most commonly affects first-time pregnancies in the second trimester of pregnancy (2-7%) and it is a leading cause of maternal and fetal morbidity and mortality (41).…”
Section: Activated Neutrophils From Preeclamptic Pregnancies Fail To supporting
confidence: 76%
“…During healthy pregnancy, the maternal immune system adapts to allow survival of a partially histoincompatible fetus, and failure of this adaptation contributes to poor placental invasion that predates the clinical onset of preeclampsia. Studies have suggested that impaired expansion of inducible Treg (iTreg) cells (40,51), particularly in the decidua, might represent a pathogenic defect in preeclampsia. A key feature of the niT-cell population that we describe is its ability to produce IL-17.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that failure of the maternal immune tolerance mechanisms precedes the development of placental ischemia and oxidative stress, both of which are known to be involved in the pathophysiology of preeclampsia (18). Clinical studies have shown that there is a decrease in the number of T Reg s in preeclamptic women compared with women with normal pregnancies (5,38,42,43). Our data echo these findings in that the T Reg population is a low percentage among total CD4 ϩ T cells isolated from RUPP rats.…”
Section: /Cd25supporting
confidence: 32%